Avaliação de Melhorias Funcionais para um IDE de SMA Embarcados - Siqueira, Elaine M. P. (2025)
The development of Embedded Multi-Agent Systems (MAS) suffers from constraints that make this process unintuitive. The use of specialized tools can facilitate the developer’s work. This article presents an analysis, restructuring, and new functionalities so that an environment dedicated to embedded MAS can allow agility and automation of processes in MAS software engineering. A usability research was conducted, applying the Technology Acceptance Model, to identify improvements reflected in a new prototype containing the proposed implementations.